Inventory and Assessment of Carbon Storage Capacity of species of Palms in Universiti Tun Husein Onn Malaysia, Main Campus, Batu Pahat, Johor Malaysia - Audu, Yunusa; Linatoc, Alona Cuevas (International Journal of Integrated Engineering, 2019)
Carbon dioxide constitutes about 0.04% of greenhouse gases in the atmosphere. Its concentration in the atmosphere influences the climate pattern of the world. The unceasing rise above the ambient level leads to global warming. The increase in CO2 release in UTHM (238.8964 ha), was due to the increasing number of more vehicles, and from other greenhouse gases release from structures, facilities and discharges from neighboring industries calls for attention. A study was conducted on eleven most common species of palms for their capacity to sequester a considerable amount of CO2. The Estimate of carbon storage of the palms plants was obtained by the assessments of the above standing biomass and their photosynthetic capacity. Results show that R. regia has the highest CO2 absorption capacity (10.61 µmol m-2 s-1) followed by O. tigillarium (7.26 µmol m-2 s-1), and W. bifurcata (6.83µmol m-2 s-1). E. guineensis has the highest aboveground biomass accumulation (0.09kg), followed by R. regia (0.05 kg). E. guineensis has the maximum biomass accumulation (15.13 kg), followed by L. chinensis (12.68 kg), then C. renda sp and R. regia with (8.54kg/8.43) on species abundance. The total standing biomass captured by all the palms species is 69.32kg (0.069 tons) of carbon. Hence, species of palms plants in UTHM have the capacities to absorb sufficient quantity of CO2 from the atmosphere thus contributing to the reducing-the effects of world-wide warming and climate alteration